SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PROMOSI KENAIKAN JABATAN PT. MNC VISION DIVISI TECHNICAL SERVICE JAKARTA MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Rosliana Rosliana; Ibnu Akil (INTI Nusa Mandiri, 2019)
Abstract - The human resources of a company greatly affect many aspects of determining the work success of the company. One process that is very important in the Human Resources Department of a company or business entity is the promotion process of promotion. In determining who are eligible to be promoted, the company has difficulty making decisions. This is due to the large number of employees who have high quality, while the number of positions needed is limited. In addition, data processing of employee appraisal in the company is still done manually, so that there is a high probability of inputting errors given the very large number of employees and a relatively long time required. For this reason, a decision support system is needed that can help the company in selecting employees to be promoted. The method used is Simple Additive Weighting which starts from identifying the problem and determining objectives, determining criteria and alternatives, determining the weight until the final results are obtained and proceed with a ranking process that will select alternatives that have been provided so that alternative employees are eligible for promotion position.